Інтелектуальна тьюторна система на основі бази знань обмежень з мітками - Вовк, Роман; Шекета, Василь (Видавництво Національного університету «Львівська політехніка», 2009)
In the given paper the formal-logical approach is introduced for the use of certainty factors in intelligible tutor¬ing system with means of constraints knowledge base for edu¬cational subject domain that allows using of parameters actual values on the basis of subjective estimations of subject domain teachers group.
Keywords: constraints; knowledge base; constraints sequence; queries constructions; constraints violation; тьюторингова система; коефіцієнт впевненості